2014 IEEE Symposium on 3D User Interfaces (3DUI) 2014
DOI: 10.1109/3dui.2014.6798847
|View full text |Cite
|
Sign up to set email alerts
|

How wrong can you be: Perception of static orientation errors in mixed reality

Abstract: Tracking technologies are becoming an affordable commodity due to the wide use in mobile devices today. However, all tracking technologies available in commodity hardware is error prone due to problems such as drift, latency and jitter. The current understanding of human perception of static tracking errors is limited. This information about human perception might be useful in designing tracking systems for the display of AR and VR scenarios on commodity hardware. In this paper we present the findings of a stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Particularly at farther distances, angular errors exceeding 15-20 degrees are very apparent and likely noticed by participants. This is similar to perceptible registration errors perceived and explicitly acknowledged by participants using other augmented reality systems (Madsen and Stenholt, 2014).…”
Section: Overall Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Particularly at farther distances, angular errors exceeding 15-20 degrees are very apparent and likely noticed by participants. This is similar to perceptible registration errors perceived and explicitly acknowledged by participants using other augmented reality systems (Madsen and Stenholt, 2014).…”
Section: Overall Resultssupporting
confidence: 77%
“…For instance, magnetic compasses can vary widely (+/-5°) in accuracy due to variability in the Earth's magnetic field, and Global Positioning Systems (GPS) can produce dynamic orientation errors on the order of +/-10° (Azuma, 1997). A recent study demonstrated that even a stationary gyroscope (in an iPad 3) demonstrates yaw drift of +/-10˚ over the course of 12-18 hours (Madsen and Stenholt, 2014). Of course, certain environments such as those characterized by tall buildings (i.e., urban canyons) or mountains, can result in even more severe positioning and relative direction errors (Duncan et al, 2013;Miura et al, 2015).…”
Section: Introductionmentioning
confidence: 99%